Expansion of Th17 Cells and Functional Defects in T Regulatory Cells Are Key Features of the Pancreatic Lymph Nodes in Patients With Type 1 Diabetes - Ferraro, Alessandra; Socci, Carlo; Stabilini, Angela; Valle, Andrea; Monti, Paolo; Piemonti, Lorenzo; Nano, Rita; Olek, Sven; Maffi, Paola; Scavini, Marina; Secchi, Antonio; Staudacher, Carlo; et al. (Diabetes (New York, N.Y.), 2011)
Autoimmune diseases, including type 1 diabetes, are thought to have a Th17-cell bias and/or a T-regulatory cell (Treg) defect. Understanding whether this is a hallmark of patients with type 1 diabetes is a crucial question that is still unsolved, largely due to the difficulties of accessing tissues targeted by the disease. We phenotypically and functionally characterized Th17 cells and Tregs residing in the pancreatic-draining lymph nodes (PLNs) of 19 patients with type 1 diabetes and 63 nondiabetic donors and those circulating in the peripheral blood of 14 type 1 diabetic patients and 11 healthy subjects. We found upregulation of Th17 immunity and functional defects in CD4(+)CD25(bright) Tregs in the PLNs of type 1 diabetic subjects but not in their peripheral blood. In addition, the proinsulin-specific Treg-mediated control was altered in the PLNs of diabetic patients. The dysfunctional Tregs isolated from diabetic subjects did not contain contaminant effector T cells and were all epigenetically imprinted to be suppressive, as defined by analysis of the Treg-specific demethylated region within the forkhead box P3 (FOXP3) locus. These data provide evidence for an unbalanced immune status in the PLNs of type 1 diabetic subjects, and treatments restoring the immune homeostasis in the target organ of these patients represent a potential therapeutic strategy.